Analyzing Mythological Constructions in Ring Advertisements Using Barthes’ Framework - Esamada Rose Nursaputri; Ni Komang Arie Suwastini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This study examines how Instagram advertisements reconstruct the cultural meaning of rings through mythological signification. Traditionally associated with interpersonal bonds, romantic commitment, and marital status, rings are increasingly being redefined through digital advertising as symbols of broader ideological values. Using Roland Barthes’ theory of mythology, this qualitative study analyses two Instagram advertisements: UNICEF India’s Promise Ring campaign and the Gabit Smart Ring advertisement. The analysis focuses on verbal text, visual imagery, colour schemes, typography, product presentation, and compositional design to identify how denotative signs are transformed into connotative meanings and ideological myths. The findings show that UNICEF resignifies the ring as a symbol of humanitarian commitment and social responsibility, while Gabit constructs the ring as a symbol of self-care, discipline, and personal optimization. Although the two advertisements promote different values—collective moral duty and individual self-improvement—they both demonstrate how advertising naturalizes culturally constructed meanings through carefully selected semiotic elements. This study contributes to advertising semiotics by extending Barthes’ mythological framework to Instagram-based visual marketing and by showing how a familiar material object can be reinterpreted through digital advertising to support competing ideological narratives.